A Bayesian approach to analyzing replicated preference tests - Dubnicka, Suzanne R. (My University, 2013)
Replicated or multiple preference tests have become important tools for assessing consistency in consumer preferences in repeated tests as well as overall consumer preference. Replicated preference tests can also provide the means for separating discriminators from non-discriminators. Despite the increasing popularity of multiple preference tests, there are few statistical tools for their analysis, especially when one is interested in assessing the consistency of consumer preferences. This paper presents flexible Bayesian methods for examining overall consumer preference and consistency of consumer preference in replicated preference tests. In particular, this paper presents Bayesian methods for forced-choice preference testing with two tests and then extends this methodology to include forced-choice preference testing with more than two tests and replicated preference testing with a no-preference or no-choice option. The methods produce intuitive and easily interpreted probabilities. These methods are applied to various replicated preferences test data from the literature.
Keywords: Forced-choice preference test; McNemar's test; Multiple preference tests; No-preference option; Statistical analysis